DETERMINANTS OF ANXIETY IN TRIMESTER III PREGNANT WOMEN IN THE WORKING AREA OF GUNUNGSARI PUSKESMAS, SERANG DISTRICT - Lisarsa, Whidy; Nuryati, Tati (Universitas Airlangga, 2024)
Mental disorders are experienced by pregnant women 10% worldwide, the occurrence of mental health disorders certainly requires the best solution, so that it can reduce the impacts that arise, such as preeclampsia/eclampsia, bleeding, increased blood pressure measurement results, and prolonged second stage. Preliminary studies found that pregnant women felt anxious, and the examination was still focused on physical examination. The purpose of the study was to see the determinants that cause anxiety in pregnant women in the third trimester, using a Cross-Sectional design and interview method using the Perinatal Anxiety Screening Scale (PASS) questionnaire, a sample for the study of 138 respondents using the total population. The primary data used was from the questionnaire. Statistical analysis using multiple logistic regression. The variables of parity, history of pregnancy complications, facilities, husband's support, and support from health workers have a significant effect on anxiety in pregnant women in the third trimester. The variable of health worker support is the most dominant on anxiety in pregnant women with an OR of 4.727. There is an influence of the variables of knowledge, parity, history of pregnancy complications, health facilities, and support from health workers, the dominant variable is the support of health workers, which is the main key to reducing anxiety in pregnant women in the third trimester. The better the support from health workers for pregnant women, the greater the opportunity for mothers to not feel anxious during their pregnancy.